PELAKSANAAN REHABILITASI SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP PENYALAHGUNA NARKOTIKA - Nickholas Hartono; Frans Simangunsong (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
In Indonesia, adolescents of productive age are frequently affected by environmental factors that lead to drug abuse. No. 1 Narcotics Law 35 of 2009 concerning Opiates was passed to diminish the quantity of medication victimizers and sellers in Indonesia. In addition, the Narcotics Law restricts the legal protection afforded to addicts and narcotics abuse victims, particularly in terms of access to social and medical rehabilitation; However, this legal protection has not been used to its full potential, resulting in the imprisonment of numerous drug addicts and abuse victims. Occur. Each opiate victimizer no matter what should gain admittance to clinical and social recovery, as per the conviction that Opiates Victimizers are casualties of the wrongdoings they carry out (Self Exploiting Casualties). The findings of the preceding research and analysis indicate that the Narcotics Law's legal protection has not yet been fully and effectively implemented, and that it does not yet operate in accordance with its directives